Bacterial quality of urinary tract in patients with alkaptonuria - Al-Tarawneh, Amjad; Al-limoun, Muhamad; Khlaifat, Ali M.; Tarawneh, Ibrahim; Mwafi, Nesrin; Khleifat, Khaled; Alqaraleh, Moath; Ahmad Mizher, Hussam Abdeljabar (Elsevier, 2023)
Background The aim of the current study is to determine whether there is an association between alkaptonuria (AKU) and urinary tract infection (UTI) by exploring the bacterial quality of the urinary tract, as most of the patients with AKU present with frequent occurrence of UT symptoms such as incomplete emptying of urinary bladder, dysuria and nocturia. Methods Study samples were collected from 22 participants; 9 from patients with AKU, 9 from individuals who were AKU carriers, and 4 people served as control. Confirmation of AKU diagnosis was established by the ferric chloride test and quantitative determination of urinary homogentisic acid (HGA) levels. Results In the ferric chloride test, the urine samples of AKU patients showed a characteristic black ring upon addition of few drops of ferric chloride solution. During urinary HGA determination, patients with AKU reported increased levels of urinary HGA as compared to carriers and controls. The following 10 bacterial species were isolated from the UT of AKU patients, carriers and controls: Sphingomonas paucimobilis, Escherichia coli, Francisella tularensis, Staphylococcus hominis, Staphylococcus haemolyticus, Leuconostoc mesenteroides, Dermacoccus nishinomiyaensis, Kytococcus sedentarius, Serratia fonticola and Granulicatella adiacens. The presence of S. paucimobilis was found in three male patients, and one female each from the carrier and control groups. Almost all study samples were positive for D. nishinomiyaensis and K. sedentarius. S. fonticola and G. adiacens were found only in AKU carrier females. Conclusions The results deduced that males show symptoms of arthritis early and more severely than females and by this it appears that there is an association between these symptoms and the percentage of bacterial infection in males that requires more accurate diagnosis and treatment to clarify such relationship. In the current study, males (patients, carriers, and controls) were more likely to have bacterial infections than females (64% vs. 36%). The 16 and 2 bacterial isolates, detected in 7 males and 2 females AKU patients, respectively revealed that male AKU patients had a 2.3-fold greater rate of bacterial infection than female AKU patients. Therefore, further studies are warranted to investigate if there's any relationship between higher incidence of bacterial infections and development of AKU-related clinical symptoms in male population.